Synthesis of CuO thin films by a direct current reactive sputtering process for CO gas sensing application. (15th February 2023) - Mahana, Debashrita; Mauraya, Amit Kumar; Kumaragurubaran, Somu; Singh, Preetam; Muthusamy, Senthil Kumar
Abstract: A direct current magnetron reactive sputtering, one of the well-known physical vapour deposition (PVD) techniques, was employed for the preparation of CuO thin films at room temperature for CO gas sensing application. The effect of the O2 gas flow ratio on the phase formation of copper oxide was studied by varying the O2 flow rate in the total flow of Ar/O2 gas mixture. Cu2 O phase was found to form at a low O2 flow ratio of 10% and gradually converted into stable CuO phase with an increase in O2 flow ratio through the intermediate phase of Cu4 O3 . The films exhibited a granular morphology, and the average grain size increased with an increase in the O2 partial flow. Single-phase CuO thin film has been obtained with 40% of O2 gas flow ratio. The evolution of the copper oxide phases with increasing O2 partial flow was also confirmed using the Cu 2p and O 1s core-levels of X-ray photoelectron spectroscopy. The CO gas sensing characteristics of the CuO thin film were examined by varying the operating temperature in the range of 200 °C–400 °C. An optimized CO sensing response of 127% has been obtained at 375 °C towards 91 ppm concentration with a response/recovery time of 161 s/99 s.